Organizational stressors and competitive anxiety in athletes: The moderating role of psychological flexibility - Zhang, W.; Ma, S.; Wu, D.; Huang, C. (International Journal of Sport Psychology, 2021)
The importance of organizational stressors has been increasingly acknowledged by researchers studying psychosocial responses in athletes. This study examined the association between the frequency of encountered organizational stressors and competitive trait anxiety, and investigated how psychological flexibility could moderate such a relationship. Within a correlational study design, 526 athletes (M = 20.0 years) from the eastern China completed a battery of self-report measures. Data were analyzed with a regression-based moderation analysis, using the PROCESS macro for SPSS. The results revealed positive relationships between the frequency of organizational stressors and competitive trait anxiety, whereas negative relationships between psychological flexibility and organizational stressors as well as competitive trait anxiety. A reduced association was observed between the frequency of organizational stressors and worry, and between the stressor frequency and concentration disruption in athletes with higher levels of psychological flexibility, compared to those with lower levels of psychological flexibility. The findings highlight the influential role of psychological flexibility in acting as a buffer against potential negative outcomes experienced by athletes in response to organizational stressors encountered in sport settings. Where possible, sport organizations and coaches should place emphasis on changing athletes` experiences of organizational stressors and developing athletes` psychological flexibility.